Metal organic-MXenes material with controllable superconducting property and preparation method thereof

The metallocene compound was inserted into the layers of MXenes material through electrochemical intercalation strategy, which solved the gap in the superconducting properties of MXenes materials, and realized the superconducting transformation and controllability of superconducting properties of MXenes, with the superconducting transformation temperature up to 10.24K.

CN119889803APending Publication Date: 2025-04-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411735172.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

There are gaps in the research on superconducting properties of existing MXenes materials, especially in the interpretation of superconducting transition temperature, superconducting phase stability and superconducting generation mechanism, and no superconducting phenomenon has been found in Ti-based MXenes materials.

Method used

Through the electrochemical intercalation strategy, the metallocene compound is effectively inserted between the layers of the multi-layer sheet MXenes material, and the ordered arrangement of organometallic compounds is used as column proppants and electron donors to improve the crystallinity of the MXenes material and achieve electron injection, thereby achieving superconducting transformation of MXenes.

Benefits of technology

The superconducting transformation of MXenes material was achieved, and a metal organic-MXenes material with controllable superconducting properties was obtained. The superconducting transformation temperature could reach 10.24K, and the superconducting properties were regulated by regulating the organometallic compounds and MXenes matrix types.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889803A_ABST
    Figure CN119889803A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of two-dimensional new materials, and particularly relates to a metal organic-MXenes material with controllable superconducting property and a preparation method thereof. The metal organic-MXenes material with the controllable superconducting property comprises sheet-shaped MXenes which are distributed in a layered mode and an organic metal compound which is perpendicular to the space between sheet layers of the sheet-shaped MXenes. The organic metal compound is a metallocene compound; the sheet-shaped MXenes are obtained by tabletting an MXene material; the MXene material is prepared by a wet chemical method or a Lewis acid molten salt method. An electrochemical intercalation strategy is utilized, effective intercalation of organic metal to the MXenes material is achieved, superconducting transformation of the MXenes is achieved through dimension reduction and electron injection, and the metal organic-MXenes material with the controllable superconducting property is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of two-dimensional new materials, and specifically relates to a metal organic-MXenes material with controllable superconducting properties and a preparation method thereof. Background Art

[0002] Van der Waals materials, also known as two-dimensional (2D) materials, are planar layer materials interconnected by weak van der Waals interactions. Among them, van der Waals layered materials, such as graphite, hexagonal boron nitride, transition metal sulfides (TMDs), transition metal carbides / nitrides (MXenes), etc., have long attracted widespread attention due to their unique structural characteristics and special physical and chemical properties. The most prominent feature of van der Waals layered materials that is structurally different from bulk materials is that atoms in each layer are connected by strong covalent bonds or ionic bonds, while layers are stacked with weak van der Waals force coupling to form van der Waals gaps, which provides unique conditions for constructing intercalated layered compounds with novel properties and can be continuously regulated. Since the successful exfoliation of graphene, the continuous development of two-dimensional materials has made the status of van der Waals layered materials increasingly prominent. For example, it provides an excellent matrix for the preparation of ultra-thin two-dimensional structures from top to bottom. At the same time, the reduction of dimensionality can also obtain novel physical properties that intrinsic materials do not have. The root cause is that the coupling between the charge, spin and lattice of each atomic layer changes, thus showing physical and chemical properties that are completely different from those of bulk materials. More interestingly, the continuous evolution of the interlayer coupling can be achieved by continuously changing the distance between the basic units, and ultimately the continuous regulation of the material's optical, electrical and magnetic properties can be achieved.

[0003] Superconductivity refers to the phenomenon that the resistance of a material completely disappears when the external temperature drops below a certain critical temperature, that is, electrons can flow completely losslessly at this time. How to achieve superconductivity in two-dimensional materials and obtain a higher superconducting transition temperature has become a common goal pursued by scientists around the world. However, single-layer two-dimensional materials often have harsh preparation conditions and poor stability in air environments, which limits their practical application and further development. The existence of vast interlayer spaces in van der Waals layered materials can directly regulate the structure and properties of the materials by introducing foreign species, and obtain novel physical and chemical properties similar to or even better than single-layer nanomaterials.

[0004] Among them, intercalation reaction is a favorable means to regulate the lattice structure and carrier density of layered materials. By introducing guest species such as atoms, molecules, and ions into the van der Waals gap of layered materials, the intrinsic properties of the bulk material such as charge, spin, lattice vibration, and band structure can be changed, thereby inducing special phase change behavior. At present, according to the driving force of intercalation and the medium in which it occurs, it can be divided into wet chemical intercalation, gas phase intercalation, electrochemical intercalation, and ion exchange intercalation. Among the many intercalation strategies, the outstanding advantage of electrochemical intercalation is that it forces the charged active substances to be embedded in the interlayers of layered materials under the action of an external electric field, so it is not limited by chemical potential and affected by concentration gradient balance. More importantly, by controlling the experimental conditions such as applied voltage, current, and time, the electrochemical intercalation strategy can also accurately regulate the stoichiometric ratio, intercalation structure, and performance of the intercalated substances, thereby realizing customized structural editing and performance-oriented design of functional materials.

[0005] However, there is a big gap in the research on the superconducting properties of MXenes, a new type of two-dimensional layered material. The existing MXenes superconductors are also limited in terms of superconducting transition temperature, superconducting phase stability, and the explanation of the superconductivity mechanism. In addition, superconductivity has not yet been found in Ti-based MXenes materials. There is also no complete theoretical prediction method and experimental verification for the superconducting properties of the MXenes material family containing rich metal elements at the M position. Summary of the invention

[0006] The purpose of the present invention is to provide a metal organic-MXenes material with controllable superconducting properties and a preparation method thereof in response to the above-mentioned technical problems, to achieve effective intercalation of organic metal compounds into MXenes materials by electrochemical intercalation strategy, and to achieve superconducting transformation of MXenes by dimensionality reduction and electron injection.

[0007] The metal organic-MXenes material with controllable superconducting properties in the technical solution of the present invention includes layered flaky MXenes and organic metal compounds perpendicular to the flaky MXenes layers; the organic metal compound is a metallocene compound.

[0008] The present invention effectively inserts the organometallic compound between the multilayer MXenes sheets. The orderly arranged organometallic compound acts as a column support and electron donor, significantly improving the crystallinity of the MXenes material and bringing about stress engineering and electron injection effects. At the same time, the superconducting properties, i.e., the superconducting transition temperature, can be regulated by selecting the types of organometallic compounds and MXenes matrix.

[0009] Metallocene compounds have versatility and a unique "sandwich" structure. They can "sandwich" many different elements and replace different ring structures to form organometallic compounds with rich physical and chemical properties. Their redox activity makes it easy for charge transfer to occur during the interaction with other species. When metallocene compounds are introduced as organometallic compounds into the interlayer of van der Waals layered materials, charge transfer can occur from the cyclopentadiene groups on both sides to the MXene matrix. At the same time, the organic-inorganic interface stress is introduced, which affects the electroacoustic coupling effect in the metal organic-MXene intercalation compound, thereby achieving superconducting transition.

[0010] Furthermore, the flake MXenes are obtained by pressing the MXene material into sheets.

[0011] Furthermore, the flake MXenes are discs with a diameter of 1 to 50 mm, preferably a diameter of 5 to 30 mm.

[0012] Preferably, the pressure during tableting is 3 to 10 MPa.

[0013] Furthermore, the molecular formula of MXene material is M n+1 X n T x , wherein M is a transition metal element, including Ti alone or Ti and one or more of V, Sc, Cr, Zr, Nb, Mo, Hf, and Ta, X is a C element and / or a N element, T is an end group, including one or more of -Cl, -Br, -I, -F, =O, -OH, -S, an alkyl group, an alkoxy group, an ether group, and an ester group, and n is 1, 2, or 3.

[0014] Furthermore, MXene materials are prepared by wet chemical methods or Lewis acid molten salt methods.

[0015] Furthermore, the organometallic compound may be one or more of cobaltocene, ferrocene, nickelocene and rhodiumocene.

[0016] Furthermore, the wet chemical method for preparing MXene materials is to add MAX phase materials into the etching solution and stir the reaction, and then wash, centrifuge or filter, and dry.

[0017] Furthermore, M in the MAX phase material is the same as M in the MXene material; X is the same as X in the MXene material; A is one or more elements of the IIIA or IVA main group, which can be listed as one or more of Al, B, Ga, In, Tl, C, Si, Ge, Sn, and Pb.

[0018] Furthermore, the etching solution is an acid solution or a mixture of an acid solution and a chloride salt.

[0019] Preferably, the chloride salt includes one or more of lithium chloride, sodium chloride and potassium chloride; the acid solution includes one or more of hydrofluoric acid, hydrochloric acid, nitric acid and sulfuric acid.

[0020] Preferably, the concentration of the acid solution is 1-50 wt %; the ratio of the chloride salt to the acid solution is 1 g: (10-100) mL.

[0021] Furthermore, the ratio of the MAX phase material to the etching solution is 1 g: (10-100) mL.

[0022] Preferably, the stirring reaction temperature is 10-60° C., the stirring speed is 200-1000 rpm, and the time is 10-100 h.

[0023] Furthermore, the Lewis acid molten salt method for preparing MXene materials is to mix MAX phase materials, Lewis acid salts and inorganic salts, react at high temperature, and then wash and dry.

[0024] Preferably, the Lewis acid salt is a Lewis acid salt including a target functional group, including but not limited to transition metal halides.

[0025] Preferably, the inorganic salt is a metal halide formed by a halogen element and a metal element.

[0026] Furthermore, the temperature of the high temperature reaction is 500-1000° C., and the time is 3-10 hours.

[0027] Preferably, the washing is performed with an acid solution and / or water having a concentration of 1 to 10 M; the centrifugal speed is 2500 to 5500 rpm; the drying temperature is 50 to 200° C., and the drying time is 1 to 10 hours.

[0028] The present invention also provides a method for preparing the above-mentioned metal organic-MXenes material with controllable superconducting properties, comprising the following steps:

[0029] Using flake MXenes as cathode, graphite rods as anode, and the precursor dispersion of organic metal compounds as electrolyte solution, a constant current is applied for electrochemical intercalation.

[0030] Furthermore, when the MXene material in the sheet-like MXenes is prepared by a Lewis acid molten salt method, the sheet-like MXenes must be pre-embedded with lithium before use.

[0031] Preferably, the pre-embedded lithium is assembled into a battery using flaky MXenes as the experimental electrode, lithium metal as the counter electrode, and a lithium bis(trifluoromethanesulfonylimide) (LiTFSI) solution with a molar mass concentration of 1 to 5 M as the electrolyte (the solvent is propylene carbonate (PC)), and discharged at a current density of 1 to 5 mA / g for 20 to 30 h.

[0032] Furthermore, the solvent used in the precursor dispersion of the organometallic compound is one or more of dimethyl sulfoxide (DMSO), propylene carbonate (PC), and acetonitrile (ACN).

[0033] Preferably, the mass concentration of the organic metal compound precursor dispersion is 1.0 to 5.0%.

[0034] Furthermore, the constant current is 1.0 to 10.0 mA, and the power is turned on for 10 to 20 hours after the constant current is applied.

[0035] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0036] (1) Using the electrochemical intercalation strategy, we can effectively intercalate organometallic compounds into MXenes materials, and achieve the superconducting transition of MXenes through dimensionality reduction and electron injection, thus obtaining a metal-organic-MXenes material with controllable superconducting properties;

[0037] (2) The present invention effectively inserts organic metal compounds into the interlayers of multilayer MXenes. The orderly arranged organic metal compounds significantly improve the crystallinity of MXenes materials and bring about stress engineering and electron injection effects;

[0038] (3) The present invention can achieve the regulation of superconducting properties, that is, superconducting transition temperature, by selecting the types of organic metal compounds and MXenes matrix, and the highest superconducting transition temperature can reach 10.24K;

[0039] (4) By adjusting the choice of solvents used in the dispersion of organometallic compounds and their precursors during the electrochemical intercalation process and the structure editing of MXenes materials, the charge transfer and stress response between the host and the guest are affected, and finally the continuous regulation of the superconducting transition temperature is achieved;

[0040] (5) The preparation method of the above-mentioned metal organic-MXenes material with controllable superconducting properties is simple and efficient, does not require the use of complex and expensive equipment, and the preparation process is environmentally friendly and green, which is conducive to promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 (a) and (b) the X-ray diffraction pattern of the metal organic-MXenes material obtained in Example 1;

[0042] Figure 2 This is a scanning electron microscope image of the metal organic-MXenes material obtained in Example 1;

[0043] Figure 3 The multilayer Ti3C2T obtained in Example 1x -High-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) images of MXenes powders and metal organic-MXenes materials (a-multilayer Ti3C2T x -MXenes powder, b-metal organic-MXenes material) and element distribution map (c);

[0044] Figure 4 The Raman image (a) and the Co 2p fine spectrum (b) in the X-ray absorption near edge structure (XANES) of the metal organic-MXenes material obtained in Example 1;

[0045] Figure 5 The electrical transport test results of the metal organic-MXenes material obtained in Example 1: (a) the resistivity changes with temperature under zero magnetic field, (b) the temperature dependence of the resistivity under different magnetic fields;

[0046] Figure 6 The magnetic properties test results of the metal organic-MXenes material obtained in Example 1: (a) isothermal magnetization curve at 2K, (b) temperature dependence of the magnetization intensity of the metal organic-MXenes material superlattice under a 50Oe magnetic field during zero field cooling and field cooling;

[0047] Figure 7 The temperature dependence of the resistivity of the metal organic-MXenes materials obtained in Examples 1-7 under zero magnetic field: DETAILED DESCRIPTION

[0048] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0049] Example 1

[0050] The method for preparing the metal organic-MXenes material with controllable superconducting properties in this embodiment comprises the following steps:

[0051] (1) 2.0 g of lithium chloride and 100 ml of a 10 wt% hydrofluoric acid solution were mixed as an etchant, and then 2.0 g of Ti3AlC2 was added and stirred at 25°C and 500 rpm for 24 h to obtain a MXenes dispersion, which was washed twice with a 6 M HCl solution and deionized water, respectively, and centrifuged at 3500 rpm to pour off the supernatant to obtain a precipitate, which was vacuum dried at 110°C for 3 h to obtain a multilayer Ti3C2T x -MXenes powder;

[0052] (2) 0.1 g of multilayer Ti3C2T x -MXenes powder was pressed into a disc with a diameter of 14 mm at a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, and a graphite rod was used as an anode. 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate was dissolved in 5 g of dimethyl sulfoxide as an electrolyte solution, and a constant current of 2 mA was applied for 12 h to drive cations into the cathode. The product was then washed with deionized water for multiple times to remove impurities and dried in vacuum at 80 °C. The obtained metal organic-MXenes material was recorded as Co-Ti3C2T x -MXene.

[0053] Example 2

[0054] The method for preparing the metal organic-MXenes material with controllable superconducting properties in this embodiment comprises the following steps:

[0055] (1) 0.5 g Ti2AlC powder was slowly added to 40 mL of 49% HF solution, stirred at 25 °C and 500 rpm for 10 h, washed with deionized water until the pH was 6, filtered and vacuum dried at 80 °C for 4 h to obtain multilayer Ti2CT for electrode material. x -MXenes powder;

[0056] (2) 0.1 g of multilayer Ti2CT x -MXenes powder was pressed into a disc with a diameter of 14 mm under a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, a graphite rod as an anode, 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate was dissolved in 5 g of dimethyl sulfoxide as an electrolyte solution, and a constant current of 2 mA was applied for 12 h to drive cations into the cathode, and then the product was washed with deionized water for multiple times to remove impurities and dried in vacuum at 80 ° C. The obtained metal organic-MXenes material was recorded as Co-Ti2CT x -MXene.

[0057] Example 3

[0058] The method for preparing the metal organic-MXenes material with controllable superconducting properties in this embodiment comprises the following steps:

[0059] (1) 0.5 g TiNbAlC powder was slowly added to 40 mL HF solution with a mass concentration of 49%, stirred at 25 ° C and 500 rpm for 19 h, washed with deionized water until the pH was 6, filtered and vacuum dried at 80 ° C for 4 h to obtain multilayer TiNbCT for electrode material x -MXenes powder;

[0060] (2) 0.1g multilayer TiNbCT x -MXenes powder was pressed into a disc with a diameter of 14 mm under a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, a graphite rod as an anode, 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate was dissolved in 5 g of dimethyl sulfoxide as an electrolyte solution, and a constant current of 2 mA was applied for 12 h to drive cations into the cathode, and then the product was washed with deionized water for multiple times to remove impurities and dried in vacuum at 80 ° C. The obtained metal organic-MXenes material was recorded as Co-TiNbCT x -MXene.

[0061] Example 4

[0062] The difference between this embodiment and embodiment 1 is that in step (1), 1.0 g of Ti2Mo2AlC3 powder is slowly added to 20 mL of HF solution with a mass concentration of 49%, stirred at 55° C. for 96 h, washed with deionized water until the pH is 6, filtered and vacuum dried at 80° C. for 4 h to obtain a multilayer Ti2Mo2C3T3O3 electrode material. x -MXenes powder, the obtained metal organic-MXenes material is recorded as Co-Ti2Mo2C3T x -MXene.

[0063] Example 5

[0064] The difference between this embodiment and embodiment 1 is that in step (1), 1.0 g of Ti3AlCN powder is slowly added to 10 mL of HF solution with a mass concentration of 30%, stirred at 25° C. for 18 h, washed with deionized water until the pH is 6, filtered and vacuum dried at 80° C. for 4 h to obtain multilayer Ti3CNT for electrode material. x -MXenes powder, the obtained metal organic-MXenes material is recorded as Co-Ti3CNT x -MXene.

[0065] Example 6

[0066] The method for preparing the metal organic-MXenes material with controllable superconducting properties in this embodiment comprises the following steps:

[0067] (1) The reagents were weighed according to the molar ratio of Ti3AlC2:CdCl2:NaCl:KCl=1:3:10:10, ground evenly in a glove box, and then transferred to a corundum crucible. The mixture was placed in a tube furnace and heated to 650°C at a rate of 5°C / min for 5 hours. The sample was taken out after natural cooling, washed with deionized water and 50 ml of 3M hydrochloric acid, and the solid was collected after filtration. The solid was dried in vacuum at 110°C for 3 hours to obtain a multilayer Ti3C2Cl2-MXenes powder.

[0068] (2) 0.1 g of multilayer Ti3C2T x -MXenes powder was pressed into a disc with a diameter of 14 mm at a pressure of 4 MPa, and a 1 M lithium bis(trifluoromethanesulfonylimide) solution was used as the electrolyte (the solvent was propylene carbonate), and lithium metal was used as the counter electrode to assemble a button cell, which was discharged at a current density of 2 mA / g for 24 h;

[0069] (3) After the discharge is completed, the battery is disassembled, and the disc active material is taken out and placed at the bottom of a graphite crucible as a cathode. The graphite rod is used as an anode. 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate is dissolved in 5 g of dimethyl sulfoxide as an electrolyte solution. A constant current of 2 mA is applied for 12 h to drive cations into the cathode. The product is then washed with deionized water for multiple times to remove impurities and dried in vacuum at 80 °C. The resulting metal organic-MXenes material is recorded as Co-Ti3C2Cl2-MXene.

[0070] Example 7

[0071] The only difference between this embodiment and embodiment 6 is that in step (1), Ti3AlC2 and CdBr2 are evenly ground in a glove box according to a molar ratio of Ti3AlC2:CdBr2=1:8, and then transferred to a corundum crucible, placed in a tube furnace and heated to 650°C at a rate of 5°C / min for 12 hours, and the sample is taken out after natural cooling, washed with deionized water and 50 ml of 3M hydrobromic acid, and the solid is collected after filtration, and vacuum dried at 60°C for 6 hours to obtain a multilayer Ti3C2Br2-MXenes powder. The obtained metal organic-MXenes material is recorded as Co-Ti3C2Br2-MXene.

[0072] Example 8

[0073] The difference between this embodiment and embodiment 1 is that in step (2), 0.1 g of multilayer Ti3C2T x-MXenes powder was pressed into a disc with a diameter of 14 mm at a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, and a graphite rod was used as an anode. 0.1 g of bis(cyclopentadienyl)iron (III) hexafluorophosphate was dissolved in 5 g of dimethyl sulfoxide as an electrolyte solution, and a constant current of 0.5 mA was applied for 12 h to drive cations into the cathode. The product was then washed with deionized water for multiple times to remove impurities and dried in vacuum at 80 °C. The obtained metal organic-MXenes material was recorded as Fe-Ti3C2T x -MXene.

[0074] Example 9

[0075] The difference between this embodiment and embodiment 1 is that in step (2), 0.1 g of multilayer Ti3C2T x -MXenes powder was pressed into a disc with a diameter of 14 mm at a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, and a graphite rod was used as an anode. 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate was dissolved in 5 g of acetonitrile as an electrolyte solution, and a constant current of 0.5 mA was applied for 12 h to drive cations into the cathode. The product was then washed with deionized water for multiple times to remove impurities and dried in vacuum at 100 °C. The obtained metal organic-MXenes material was recorded as Co-Ti3C2T x -MXene-ACN.

[0076] Example 10

[0077] The difference between this embodiment and embodiment 1 is that in step (2), 0.1 g of multilayer Ti3C2T x -MXenes powder was pressed into a disc with a diameter of 14 mm at a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, a graphite rod as an anode, 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate was dissolved in 5 g of propylene carbonate as an electrolyte solution, and a constant current of 0.5 mA was applied for 12 h to drive cations into the cathode, and then the product was washed with deionized water for multiple times to remove impurities, and dried in vacuum at 80 °C. The obtained metal organic-MXenes material was recorded as Co-Ti3C2T x -MXene-PC.

[0078] Embodiment 11

[0079] The difference between this embodiment and embodiment 1 is that in step (2), 0.1 g of multilayer Ti3C2T x-MXenes powder was pressed into a disc with a diameter of 14 mm at a pressure of 4 MPa, and the disc was placed at the bottom of a graphite crucible as a cathode, a graphite rod as an anode, 0.1 g of bis(cyclopentadienyl)cobalt(III) hexafluorophosphate was dissolved in 5 g of dimethyl sulfoxide as an electrolyte solution, and a constant current of 0.5 mA was applied for 12 h to drive cations into the cathode, and then the product was washed with deionized water for multiple times to remove impurities, and dried in vacuum at 80 °C. The obtained metal organic-MXenes material was recorded as Co-Ti3C2T x -MXene-DMSO.

[0080] The electrical transport test process is as follows: weigh 60 mg of MXenes material, apply a pressure of 2 MPa to press it into a 10 mm*10 mm block material, use the Van der Pauw method to contact the sample through a copper probe, use the physical property comprehensive measurement system (PPMS-9) to measure the resistivity change with temperature (RT) curve, apply a vertical magnetic field of 0.5T to 9T, and observe the changes in the RT curve under magnetic fields of different intensities.

[0081] The magnetic properties test process is as follows: weigh 60 mg of TiMXenes material, apply a pressure of 2 MPa to press it into a 5 mm*5 mm block material, and use a magnetic measurement system (MPMS-SQUID) to perform field cooling (FC) and zero field cooling curve (ZFC) tests, and record the change curve of the sample magnetic permeability with temperature under a constant H=50 Oe.

[0082] Example 1 Metal organic-MXenes material Co-Ti3C2T x -MXene’s XRD pattern is as follows Figure 1 As shown in (a), it can be seen that the characteristic peak (002) of MXenes after intercalation moves significantly to a lower angle, and the crystal order of the material itself is greatly improved. The infrared spectrum ( Figure 1 (b) shows that the characteristic peaks of the intercalated organic metal still exist in the product, proving the stability and effectiveness of electrochemical intercalation; SEM images are shown in Figure 2 As shown in FIG. 1 , it can be seen that the Co element is evenly distributed on the MXenes particles, which further proves the reliability of the electrochemical intercalation method in the present invention; the high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) is shown in FIG. Figure 3 As shown in the figure, it can be seen that the interlayer spacing of the MXenes material arranged layer by layer after intercalation is significantly expanded, the size is basically consistent with the XRD characterization results, and the cobalt cyclopentadienyl is evenly distributed inside the material; Raman spectrum Figure 4(a) The effect of intercalated organic metals on MXenes materials is further characterized. It can be seen that after intercalation, the A1g (Ti, O, C) vibration peak of the MXenes material is red-shifted, and A1g (C) is blue-shifted, which is closer to the characteristic peak position of few-layer MXene. This is closely related to the weakening of the coupling between layers caused by the reduction of dimensionality and the electron injection brought by organic metals. It can be calculated by the formula that the MXenes matrix structure has a strain of 4.9%, Figure 4 (b) XANES also provides strong evidence for the change in the valence of Ti in the MXenes material after intercalation. Due to the injection of electrons, the valence of Ti is significantly reduced.

[0083] like Figure 5 As shown in the figure, when the test temperature starts to decrease from 300K, the resistivity of the sample gradually decreases. At 8.31K, the resistivity of the sample drops sharply, that is, the superconducting transition begins. At 5.59K, the resistivity completely changes to 0, and the sample turns into a superconducting state. As the external magnetic field is gradually increased, the superconducting transition temperature gradually decreases until the superconducting transition disappears. Field cooling and zero field cooling curve test (such as Figure 6 a. Figure 6 b), further proves that the metal organic-MXenes material obtained in Example 1 has complete anti-magnetism, that is, it conforms to the Meissner effect, and the transition temperature is consistent with the RT curve test result. Therefore, the obtained metal organic-MXenes material has both zero resistance effect and complete anti-magnetism, proving that it does have superconducting properties.

[0084] like Figure 7 As shown in (a), replacing the M3C2 layer with the M2C layer will make the Co-Ti2CT x -MXene in T c = 9.51 K, which is attributed to the enhanced electron-phonon interaction within the in-plane MXene sheet and the enhanced interlayer coupling outside the plane; when some Ti atoms are replaced by Nb atoms to form M'M"C (M' and M" represent different transition metals) layers, the Co-TiNbCT obtained in Example 3 x -MXene’s T c Slightly decreased to 8.25K, on ​​the contrary, the thicker layer gave the Co-Ti2Mo2C3T obtained in Example 4 x -MXene’s T c The lower one is 6.40K, which is mainly due to the hindered interlayer coupling and the widening of the band gap; the change of the X position to a mixture of C and N atoms also has a negative impact on the carrier density, resulting in the Co-Ti3CNT obtained in Example 5 x -MXene’s T c Lower, 6.38K, such as Figure 7(b) As shown; the surface end group, as the outermost atom of the MXene crystal structure, plays a key intermediary role in the charge transfer between the host and the guest insert. Examples 6 and 7 also measured the RT curve. Figure 7 As can be seen in (c), its changing trend is T c (-T x )>T c (-Cl)>T c (-Br), the coupling effect between the lattice vibration of MXene and the surface functional groups makes the Ti3C2T x With the highest T c , which is attributed to the enhancement of charge transfer or phonon scattering, resulting in stronger electroacoustic coupling; the introduction of different organic metals in the interlayer region can fundamentally regulate the electronic properties of the MXene hybrid superlattice. The Fe-Ti3C2T obtained in Example 8 x -MXene electrical transport characterization Figure 7 As shown in (d), it can be seen that after replacing the Co-containing metal organic intercalant with Fe, the superconducting transition temperature is significantly increased, which is related to the latter transferring more electrons to the MXenes matrix material and bringing about a larger lattice strain. At the same time, the use of different organic solvents (such as DMSO, PC and ACN) can also achieve different co-intercalation processes, providing a general mechanism for interlayer conduction.

[0085] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A metal organic-MXenes material with controllable superconducting properties, characterized in that: It includes layered flaky MXenes and organic metal compounds perpendicular to the flaky MXenes layers; the organic metal compound is a metallocene compound.

2. The metal organic-MXenes material with controllable superconducting properties according to claim 1, characterized in that: Flake MXenes are obtained by pressing MXene materials into sheets.

3. The metal organic-MXenes material with controllable superconducting properties according to claim 1, characterized in that: Flake MXenes are discs with a diameter of 1 to 50 mm.

4. The metal organic-MXenes material with controllable superconducting properties according to claim 1, characterized in that: The molecular formula of MXene material is M n+1 X n T x , wherein M is a transition metal element, including Ti alone or Ti and one or more of V, Sc, Cr, Zr, Nb, Mo, Hf, and Ta, X is a C element and / or a nitrogen element, T is an end group, including one or more of -Cl, -Br, -I, -F, =O, -OH, -S, an alkyl group, an alkoxy group, an ether group, and an ester group, and n is 1, 2, or 3.

5. The metal organic-MXenes material with controllable superconducting properties according to claim 2, characterized in that: MXene materials are prepared by wet chemical methods or Lewis acid molten salt method.

6. The metal organic-MXenes material with controllable superconducting properties according to claim 5, characterized in that: The wet chemical method for preparing MXene materials is to mix chloride salt and acid solution as an etchant, then add MAX phase material and stir to react, and then wash, centrifuge or filter, and dry.

7. The metal organic-MXenes material with controllable superconducting properties according to claim 5, characterized in that: The Lewis acid molten salt method for preparing MXene materials is to mix MAX phase materials, Lewis acid salts and inorganic salts, react at high temperature, and then wash and dry.

8. The method for preparing a metal organic-MXenes material with controllable superconducting properties according to any one of claims 1 to 7, characterized in that: The following steps are involved: Using flake MXenes as cathode, graphite rods as anode, and the precursor dispersion of organic metal compounds as electrolyte solution, a constant current is applied for electrochemical intercalation.

9. The preparation method according to claim 8, characterized in that: When the MXene material in the sheet-like MXenes is prepared by a Lewis acid molten salt method, the sheet-like MXenes must be pre-embedded with lithium before use.

10. The preparation method according to claim 8, characterized in that: The solvent used in the precursor dispersion of the organometallic compound is one or more of dimethyl sulfoxide, propylene carbonate and acetonitrile.